2016
DOI: 10.1088/1748-6041/11/1/015013
|View full text |Cite
|
Sign up to set email alerts
|

Controlled mineralisation and recrystallisation of brushite within alginate hydrogels

Abstract: Abstract. Due to high solubility and resorption behaviour under physiological conditions, brushite (CaHPO 4 ·2H 2 O, calcium monohydrogen phosphate dihydrate, dicalcium phosphate dihydrate) has great potential in bone regeneration applications, both in combination with scaffolds or as component of calcium phosphate cements. The use of brushite in combination with hydrogels opens possibilities for new cell based tissue engineering applications of this promising material. However, published preparation methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…We have previously shown the potent effect of brushite seed crystals on phase selection within alginate hydrogels and with the added benefit of our spatiotemporal characterization toolbox we further investigate this effect here. [15] It has previously been shown that alginate, and especially the guluronate residues (Gblocks) which have a high affinity for calcium, have an inhibitory effect on the nucleation (and growth) of calcium phosphate crystals. [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown the potent effect of brushite seed crystals on phase selection within alginate hydrogels and with the added benefit of our spatiotemporal characterization toolbox we further investigate this effect here. [15] It has previously been shown that alginate, and especially the guluronate residues (Gblocks) which have a high affinity for calcium, have an inhibitory effect on the nucleation (and growth) of calcium phosphate crystals. [16].…”
Section: Resultsmentioning
confidence: 99%
“…This approach allows control over the resulting CaP phase and has recently been investigated in particular for the formation of HAp and brushite. [14,15] In order to produce phase pure alginate-brushite composites, seed crystals were used to initiate nucleation, since conditions which normally produce brushite when precipitated in solution, resulted in HAp inside the gel network, irrespective of the precursor concentrations and initial pH. [15] Further investigation into this phenomena revealed an inhibitory effect of alginate on the growth and nucleation of brushite in the presence of small amounts of alginate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these stimuli-responsive features of the hydrogel have shown to be very useful in controlling drug release [1] or to be useful for label-free and specific sensing of biomolecules [19,22]. Other properties of the gel-polymer network may also be of importance for the crystallization of minerals [4,23] or for the nucleation and growth of metal nanoparticles made by chemical reduction in the nano-fillers of the hydrogel matrix [24,25]. These hydrogels embedded with noble metal nanoparticles (NMNP) are fascinating materials often utilized for wound healing [26,27] but also impressive materials as nanoplasmonic systems [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…15 A recent study conducted in our group showed alginate hydrogels mineralized with brushite were potential candidates for bone tissue engineering applications. 16 Incorporation of bioceramics in alginate hydrogels enhances both the mechanical properties and the bioactivity of the polymer network. Brushite was chosen as the mineral phase due to its high solubility among calcium phosphates under physiological conditions, which enables for ready transformation and bone remodeling by providing necessary space and ion source for bone-like mineral formation in vivo.…”
Section: Introductionmentioning
confidence: 99%